(3GdBdI GdQUOjI GdeSeGI HPGJ GdcQSjs - (3eMeO Hf Ydj GdMejOj GdQhej GdMfaj,J (B1179 (3g` s
(3ChdgG (B:s
(3fMeOc jGef jOhQ Gdadc hHYO , ajbhd deG cGfJ PGJ GdcQSi ef GdBdGJ GdQUOjI cKjQI GdeMUhd , jSjQI GdMUhd , heY gPG eJQhcI GdYed aj GdHdGO s
(3BNQgG (B:s
(3gh eWGdY GdhbJ , hEf TFJ aRO GdeGVi ef GdfgGQ Ydi eWGdY GdTQhb , ChQO GdeGVi ef Gddjd Ydi eWGdY GdZQhH , aGdMGUd gh GdeWdhH hdjcf gPG BNQ eG ChQOfGg hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B5s
(3HgG WeSs
(3CdagG SfI (B1160 (3g`s
(3hQJHgG Ydi ebOeI h (B18 (3HGHkGs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs